Find the measure of angle IHG in the picture.
Find the measure of angle IHG in the picture. - 1

Answers

Answer 1
Answer: Set 12x + 13 equal to Angle ZHG plus Angle IHZ. x=10 and the measure of Angle IHG should be 133.

Related Questions

Solve for x: 3|2x − 2| + 6 = 18. x = 3, x = −3 x = 3, x = −1 x = 1, x = −1 x = −3, x = 1
The cost of $500,000 worth of 20-year term life insurance for Derek is $96.21 per month. If Derek's employer covers 85% of this cost, how much is deducted from Derek's gross income per year for life insurance?
What value for c will make the expression a perfect square trinomial? x2 – 7x + c
A function is shown in the table.x g(x) −2 2 −1 −3 0 2 1 17 Which of the following is a true statement for this function? (A)The function is increasing from x = −2 to x = −1. (B)The function is increasing from x = 0 to x = 1. (C)The function is decreasing from x = −1 to x = 0. (D)The function is decreasing from x = 0 to x = 1.
13 is to 8 as x + 4 is to x

16/6 to mixed fraction

Answers

16/6 as a mixed fraction is 2 2/3.
Hope this helps.

-5, _____, _____, 7, 11

Answers

Answer:

the missing numbers are -1, 3,

Step-by-step explanation:

11-7=4

sooo

-5+4= -1

-1+4=3

570 mL = ? oz,show work

Answers

Conversion from milliliters to ounces can be done using the following relation: 1 mL = 0.033814 ounce.

Given 570mL, we multiply it to the amount of ounces as shown in the relation. This is done below:

570 mL * (0.033814 oz / 1 mL) = 19.274 oz

Solve by graphing
y= -4x+5
y=3x-2

Answers

y = -4x + 5
y = 3x - 2

  -4x + 5 = 3x - 2
+ 4x       + 4x
           5 = 7x - 2
        + 2        + 2
           7 = 7x
           7     7
           1 = x
           y = -4x + 5
           y = -4(1) + 5
           y = -4 + 5
           y = 1
     (x, y) = (1, 1)

Activity 4: Factor Then solve1. x^2+7x=0
2. 6s^2+18s=0
3. t^+8t+16=0
4. x^2-10x+25=0
5. h^2+6h=16
6. x^2-14=5x
7. 11r+15=-2r^2
8. x^2-25=0
9. 81-4x^2=0
10. 4s^2+9=12s


PLEAAASE HELP ME!

Answers

very complex, you should ask each individual question, or give more points
general strategy:
get 1 side to equal 0
factor
set each factor to 0
solve


1. factor out the x and set each to zero
x(x+7)=0
x=0

x+7=0
subtract 7
x=-7
x=0 or -7



2. factor out the 6s
6s(s+3)=0
6s=0
s=0

s+3=0
subtract 3
s=-3
s=-3 or 0



3.  I'm assuming that the equation was supposed to be t^2+8t+16 so
find what 2 numbers multiply to get 16 and add to get 8
the numbers are 4 and 4
factor
(x+4)(x+4)=0
x+4=0
subtract 4
x=-4




4. find what 2 numbers multipy to get 25 and add to get -10
the numbers are -5 and -5
factor
(x-5)(x-5)=0
set each to zero
x-5=0
add 5
x=5



5. subtract 16 from both sides
h^2+6h-16=0
find what 2 numbers multiply to get -16 and add to get 6
the numbers are -6 and 10
factor
(h-6)(h+10)=0
set each to zero
h-6=0
add 6
h=6

h+10=0
subtract 10
h=-10
h=-10 or 6



6.subtract 5x from both sides
x^2-5x-14=0
find what 2 numbers multiply to get -14 and add to get -5
the numbers are -7 and 2
factor
(x-7)(x+2)=0
set each to zero
x-7=0
add 7
x=7

x+2=0
subtract 2
x=-2
x=-2 or 7




7.add 2r^2 to both sides
2r^2+11r+15=0
difficult so multiply 2 and 15 and get 30
not factor and find what 2 numbers multiply to get 30 and add to get 11
the numbers are 5 nd 6
split 11 up into 5 and 6
2r^2+6r+5r+15=0
group and factor
(2r^2+6r)+(5r+15)=0
factor
2r(r+3)+5(r+3)=0
reverse distribute
(2r+5)(r+3)=0
set each to zero
2r+5=0
subtract 5
2r=-5
divide 2
r=-5/2

r+3=0
subtract 3
r=-3
r=-3 or -5/2




8. this is a difference of 2 perfect squares in which if you have
x^2-y^2 that factors out of (x-y)(x+y) so
x^2-25=0
x^2-5^2=0
(x-5)(x+5)=0
set each to zero
x-5=0
add 5
x=5

x+5=0
subtract 5
x=-5
x=-5 or 5



9. differnce of 2 perfect squares
81-4x^2=0
9^2-(2x)^2=0
(9-2x)(9+2x)=0
set each to zero
9-2x=0
add 2x to both sides
9=2x
divde 2
9/2=x

9+2x=0
subtract 9 from both sidees
2x=-9
divide 2
x=-9/2
x=-9/2 or 9/2


10. subtract 12s from both sides
4s^2-12s+9=0
multiply 4 and 9 and get 36
find what 2 numbers multiply to get 36 and add to get -12
the numbers are -6 and -6
split up the -12s into -6s and -6s
4s^2-6s-6s+9=0
group
(4s^2-6s)+(-6s+9)=0
factor
2s(2s-3)+(-3)(2s-3)=0
reverse distribute
(2s-3)(2s-3)=0
set each to zero
2s-3=0
add 3
2s=3
divide 2
s=3/2









ANWERS:
1. x=0 or -7
2. s=-3 or 0
3. x=-4
4. x=5
5. h=-10 or 6
6. x=-2 or 7
7. r=-3 or -5/2
8. x=-5 or 5
9. x=-9/2 or 9/2
10. s=3/2

What is the slope of (12, -18), (11,12)

Answers

Answer: -30

Step-by-step explanation:

    We can use the given formula to find the slope. This finds the change in y over the change in x.

         \displaystyle (y_(2) -y_(1) )/(x_(2) -x_(1) ) =(12--18)/(11-12) =(30)/(-1) =-30